ANALYSIS OF 8 GRADER STUDENTS’ PERFORMANCE AT SMP AM IN UNDERSTANDING THE TRIANGLE CONCEPT BASED ON NCTM GEOMETRY STANDARD: ANALISIS KINERJA SISWA KELAS 8 SMP AM DALAM MEMAHAMI KONSEP SEGITIGA BERDASARKAN STANDAR GEOMETRI NCTM - Prameswari, Balqis; Haryani, Faradillah (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
Geometry plays a pivotal role in mathematics education, contributing significantly to the development of students' spatial awareness, intuition, and visualization skills. Despite its importance, there are reported challenges in students' understanding of geometry, with the Merdeka curriculum geometry standard noted for not adequately emphasizing the fundamental understanding of triangle properties before introducing congruence. Conversely, studies have highlighted the effectiveness of incorporating NCTM (National Council of Teachers of Mathematics) standards in fostering mathematical comprehension in this domain. This research study delves into the performance of eighth-grade students in comprehending triangle concepts, guided by the NCTM geometry standard. Employing a content analysis technique on student work, created based on NCTM indicators and assessed accordingly, the study reveals deficiencies in students' understanding. These challenges include difficulties in describing and categorizing triangles, identifying angle relationships, constructing logical arguments using both inductive and deductive reasoning, and recognizing relationships between side lengths. These findings underscore the urgent need to address these knowledge gaps and bridge the disparity between NCTM standards and students' current comprehension levels regarding triangle concepts.